CRIMINAL LIABILITY OF MEDICAL RESPONSIBILITY IN HANDLING OF PATIENTS WITH GASTROINTESTINAL DISORDERS - OK Isnainul; Mulyadi Mulyadi; Idwan Harris Siahaan (Magister Kenotariatan Universitas Pasundan, 2022)
Errors that can occur in medical actions from medical personnel include gastrointestinal handling. Gastrointestinal is commonly found in the intensive care unit (ICU). Errors or omissions are an essential element to determine whether or not a person can be sentenced to a crime, as well as in medical malpractice actions, it is largely determined by the presence or absence of negligence or errors of medical personnel in carrying out medical actions against patients, both professionally and legally. The purpose of the study was to analyze “Criminal Liability of Medical Personnel who are Negligent in Handling Patients with Gastrointestinal Disorders”. The results of the study obtained: 1) Criminal provisions against medical personnel who are negligent in handling patients with gastrointestinal disorders are regulated in Article 51 of the Republic of Indonesia Law Number: 29 of 2004 concerning medical practice, where a medical worker is obliged to provide assistance on a humanitarian basis. Looking at these provisions, it can be seen that the medical profession requires special competence and authority because the actions taken contain considerable risks. Medical personnel in carrying out medical procedures already have service standards that serve as guidelines and guidelines that apply to all medical personnel. If the standard is not implemented or implemented but is not in accordance with the required average standard, in the sense of ignoring the obligations stipulated by the applicable laws and regulations and the code of ethics of the medical profession, then it can be said as an error in the form of culpa or negligence. 2) Criminal liability of medical personnel for negligence in handling patients with gastrointestinal disorders is a criminal act by which, of course, can be subject to criminal provisions or sanctions. Criminal provisions that can be applied to medical personnel who are negligent in providing treatment to patients with gastrointestinal disorders are regulated in the general criminal provisions of Articles 267, 299, 304, 322, 344, 346, 347, 348 and Article 349 of the Criminal Code, which includes acts of a deliberate nature. As for what includes negligence, it is stated in Article 359, Article 360, and Article 361 of the Criminal Code, 3) The rights of health workers to the demands of patients with gastrointestinal disorders have been regulated through laws and regulations, namely Article 11 paragraph (1) of the Republic of Indonesia Law Number: 36 of 2014 concerning Health Workers and Article 50 of the Republic of Indonesia Law: Number 29 of 2004 concerning Medical Practice.